Environmental criminal offences - victimless crimes? - Batrićević Ana (Temida, 2013)
Ecological criminal offences, the most serious forms of harming and threatening of environment or its integral parts, represents a global phenomenon of great social hazard. They are often connected with organized transnational criminality, criminal offences against life and bodily integrity, corruption, tax evasion and discrimination. Disputable nature of the subject these incriminations protect imposes a question: “Who are the victims of ecological criminal offences - individuals, social groups, entire society or environment as value per se?” Perceiving ecological criminal offences as victimless crimes diminishes their importance and the circle of subjects interested to unveil, prove, prevent, suppress and impose punishments for these offences. Therefore, the author discusses the sustainability of the traditional, anthropocentrically defined term of victim in the context of biocentrism and its growing influence on criminal law, criminology and victimology. Attempting to determine whether ecological criminal offences represent victimless crimes, the author analyzes their term, characteristics and significance. Starting from the traditional definition of victim, she analyzes the term of “victimless crimes“ and its (un)sustainability in the context of environmental crime, focusing on its most frequent victims and the necessity of their protection.